Negative Impacts of COVID-19 Induced Lockdown on Changes in Eating Behavior, Physical Activity, and Mental Health as Modified by Digital Healthy Diet Literacy and eHealth Literacy - Nguyen, Tham T.; Nguyen, Minh H.; Pham, Thu T. M.; Le, Vinh-Tuyen T.; Nguyen, Tan T.; Luong, Thuc C.; Do, Binh N.; Dao, Hung K.; Nguyen, Huu C.; Ha, Tung H.; Pham, Linh V.; Nguyen, Phuoc B.; et al. (Frontiers in Nutrition, 2021)
Background The COVID-19-induced lockdown has been implemented in many countries, which may cause unfavorable changes in lifestyles and psychological health. People's health literacy, healthy diet, and lifestyles play important roles in mitigating the negative impacts of the pandemic. Therefore, we aimed to examine associations of COVID-19 lockdown with changes in eating behavior, physical activity, and mental health; and the modification effects by digital healthy diet literacy (DDL) and eHealth literacy (eHEALS) on the associations. Methods We conducted an observational study on 4348 outpatients from 7th April to 31st May 2020. Data from 11 hospitals in Vietnam included demographic characteristics, DDL, eHEALS, eating behavior, physical activity, and mental health changes. Multiple logistic regression and interaction models were performed to examine associations. Results Patients under lockdown had a lower likelihood of having ‘unchanged or healthier’ eating behavior (odds ratio, OR, 0.38; 95% confidence interval, 95%CI, 0.29 to 0.51; p < 0.001), ‘unchanged or more’ physical activity (OR, 0.79; 95% CI, 0.69 to 0.90; p < 0.001), and ‘stable or better’ mental health (OR, 0.77; 95% CI, 0.67 to 0.89; p < 0.001), as compared to those after lockdown. In interaction models, as compared to patients after lockdown and with the lowest DDL score, those under lockdown and with a one-score increment of DDL had a higher likelihood of having ‘unchanged or healthier’ eating behavior (OR, 1.05; 95% CI, 1.02 to 1.07; p < 0.001), and ‘stable or better’ mental health (OR, 1.02; 95% CI, 1.01 to 1.04; p < 0.001). Similarly, as compared to patients after lockdown and with the lowest eHEALS score, those under lockdown and with a one-score increment of eHEALS had a higher likelihood of having an ‘unchanged or more’ physical activity (OR, 1.03; 95% CI, 1.01 to 1.05; p < 0.001). Conclusion The COVID-19 lockdown measure could negatively affect eating behavior, physical activity, and mental health among outpatients. Better DDL and eHEALS were found to mitigate the negative impacts of the lockdown, which may empower outpatients to maintain healthy lifestyles and protect mental health. However, this study holds several limitations that may undermine the certainty of reported findings.